Evaluating the Impact of Employing Local Tax Collectors to Improve State-Level Licensing Program Outcomes in Florida. (February 2019) - Alvarez, Sergio; Bampasidou, Maria; Solís, Daniel
The improvement of public services is an important public policy objective, and several approaches have been proposed and implemented across all levels of government to achieve this goal. A recent policy in Florida (FL) fosters collaboration between local and state governments by allowing local tax collector (TC) offices to receive and support applications for the state's concealed weapons (CW) license program. We use 80, 020 application records to estimate process improvements brought about by this policy. Our analysis shows that by using TCs, the time for the application to be processed was one third the time it needed via mail and about 3% at the regional office. The likelihood of errors in applications and supporting documents decreased significantly. The policy, therefore, has improved the effectiveness of the CW licensing service in FL. Similar initiatives can be adopted by government entities facing bottlenecks in permitting or licensing processes.